Gynecologic oncology patients in the surgical high dependency unit: An analysis of indications - Thomakos, N.; Zacharakis, D.; Rodolakis, A.; Zagouri, F.; Papadimitriou, C.A.; Bamias, A.; Dimopoulos, M.-A.; Haidopoulos, D.; Vlahos, G.; Antsaklis, A. (Archives of Gynecology and Obstetrics, 2014)
Purpose: The establishment of high dependency units (HDUs) has been an undoubted advance in the management of patients undergoing major oncological procedures. The aim of this study was to examine the impact of various preoperative and perioperative patients' characteristics on the prolonged HDU stay. Methods: We conducted a retrospective study including all gynecologic oncology patients who underwent surgical management and were admitted postoperatively to our hospitals' HDU from 2006 to 2010. Results: A total of 1,014 patients were transferred to the HDU and divided into two groups according to the length of HDU stay. Group A consisted of 840 (82.8 %) patients who stayed in the HDU for ≤24 h and Group B included 174 (17.2 %) patients who remained in the HDU under close observation for >24 h. Older age was the only preoperative characteristic that remained significantly associated with HDU prolonged stay. In addition, three intraoperative factors such as use of invasive hemodynamic monitoring, bowel resection and estimated blood loss were proved to be independently associated with prolonged HDU stay. Conclusion: Certain characteristics could identify those patients who are more likely to benefit most from HDU admission. © 2014 Springer-Verlag.
Keywords: Gynecology oncology; High dependency units; Indications